KOMPETENSI KEPALA SEKOLAH SEBAGAI SUPERVISOR PEMBELAJARAN DALAM UPAYA PENINGKATAN KOMPETENSI GURU - Akhmad Afroni (IAIN Pekalongan, 2009)
The function of a head master interesting to observe because the appointment system not yet to require professional competence (as administrator, manager, education leader and education supervisor) as judgement criteria. As administrator he must be able to effeciency the source with optimal. As manager he must be able to working together with otherpeople in school work organization, and as a education leader he must be able to coordinating and moving all human potency to realize education purpose. As Supervisor he must help teacher increase them capacity in giving the lesson to the pupil as optimal.